Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus, Dana Bagi Hasil dan Jumlah Penduduk terhadap Kinerja Keuangan Pemerintah Daerah - Neneng Widowati; Deden Mulyana; Apip Supriadi (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to determine and analyze the influence of local revenue, general allocation funds, special allocation funds, profit sharing funds and population on financial performance. The study was conducted at district/city governments in West Java Province in 2014-2023. The sample size was set at 27 districts/cities with observation data from 2014 to 2023. The type of data used is secondary data in the form of panel data. The data analysis technique used is multiple linear regression with the Eviews application. The results of this research show that: 1) local original income, special allocation funds, profit sharing funds, population and regional government financial performance have an increasing trend. Meanwhile, general allocation funds have a downward trend; 2) local original income, general allocation funds, special allocation funds, profit sharing funds and population simultaneously influence the financial performance of regional governments; 3) Original regional income has a positive and significant effect on regional government financial performance. General allocation funds and population have an insignificant negative effect on local government financial performance. Special allocation funds have a negative and significant effect on local government financial performance. Profit sharing funds have an insignificant positive effect on local government financial performance.